The confluence of economics and politics in an increasingly globalized society (Texas Journal of Multidisciplinary Studies, 2025)
This article explores the discipline of International political economy (IPE) and how politics and economics interact within a globalized environment. It discusses several theoretical frameworks, such as mercantilism, liberalism, Marxism, and constructivism, to fully understand how institutions and states shape economic policy. The article also examines significant issues in the International political economy (IPE) like protectionism in global trade, the functioning of international financial institutions, economic inequality, and global warming, and offers pragmatic solutions to these problems. It ends with examining possible trends emphasizing the increasing power of digital economies, geopolitical changes, and sustainable development in influencing world economic policies.